Leader Inclusiveness and Taking Charge: The Role of Thriving at Work and Regulatory Focus - Li, Nan; Guo, Qiu-Yun; Wan, Hua (Frontiers in Psychology, 2019)
Based on self-determination theory, this study developed and tested a moderated mediation model to explore the effect of leader inclusiveness on employee taking charge behavior in addition to the mediating role of thriving at work and the moderating role of regulatory focus in this relationship. We tested the model with a sample of 206 employees from a large state-owned firm in China. Structural equation modeling revealed that leader inclusiveness was positively related to thriving at work, which in turn influenced taking charge. Promotion focus significantly moderated the relationship between leader inclusiveness and thriving at work and the mediating effect of thriving at work. As a result, the relationship and its mediating mechanism became stronger when the promotion focus of employees was high.